Implementasi Human Capital Management Dalam Manajemen Pegawai Negeri Sipil - Fajar Iswahyudi (Jurnal Transformasi Administrasi, 2018)
Currently, personnel administration is projected to implement the concept of Human Capital Management. However, personel administration has not achieved the expected goal of producing professional public servant. The purpose of this article is to analyze the implementation of Human Capital Management on personnel management. The research is arranged by literature research method. The conclusion obtained that the practice of personel management has not fully implemented the concept of Human Capital Management. This is occur in the aspects of procurement, promotion, performance appraisal, payroll, discipline, and pensiun and pensiun benefits that have not yet implemented the concept of Human Capital Management. Personnel management still combines several concept like Personnel Management, Human Resources Management, and Human Capital Management.